OPTICAL-RADIO TIME DELAYS IN Q0957+561 - Oknyanskij, V. L. (Одеські астрономічні публікації, 2017)
Applying a specific cross-correlation method, we obtained evidence that changes in the radio flux appear to lag behind the optical variations of the quasar by about 6.4 years. Our analysis of rapid continuum variations gave some constraints on the sizes and on the differences between locations of radio and optical sources. In particular, it appears that the compact radio source may be so small that it can be affected by microlensing.